2006
DOI: 10.1002/dvdy.20802
|View full text |Cite
|
Sign up to set email alerts
|

Understanding mechanisms of γ‐globin gene regulation to develop strategies for pharmacological fetal hemoglobin induction

Abstract: The developmental regulation of ␥-globin gene expression has shaped research efforts to establish therapeutic modalities for individuals affected with sickle cell disease (SCD). Fetal hemoglobin (Hb F) synthesis is high at birth, followed by a decline to adult levels by 10 months of age. The expression of ␥-globin is controlled by a developmentally regulated transcriptional program that is recapitulated during normal erythropoiesis in the adult bone marrow. It is known that naturally occurring mutations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 158 publications
0
37
0
3
Order By: Relevance
“…Several agents have been shown to have this property when studied in human or primate systems. 3 These include the nucleoside analog DNA methyltransferase (DNMT) inhibitors 5-azacytidine (5-Aza) and 2Јdeoxy-5-azacytidine (decitabine), sodium butyrate and derivatives, histone deacetylase (HDAC) inhibitors, and cytotoxic agents including hydroxyurea, cytosine arabinoside, and vinblastine. While all of these agents are active, none exhibit the optimal combination of safety, efficacy, and convenience of use that would make them applicable to most hemoglobinopathy patients, especially those who lack access to modern medical facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several agents have been shown to have this property when studied in human or primate systems. 3 These include the nucleoside analog DNA methyltransferase (DNMT) inhibitors 5-azacytidine (5-Aza) and 2Јdeoxy-5-azacytidine (decitabine), sodium butyrate and derivatives, histone deacetylase (HDAC) inhibitors, and cytotoxic agents including hydroxyurea, cytosine arabinoside, and vinblastine. While all of these agents are active, none exhibit the optimal combination of safety, efficacy, and convenience of use that would make them applicable to most hemoglobinopathy patients, especially those who lack access to modern medical facilities.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recent reviews present these 2 models as the leading candidates to explain DNMT inhibitor induction of HbF. 3,11,12 Each of the models makes specific predictions that can be experimentally tested. To determine which model best accounts for the activity of 5-Aza, we have developed an in vitro erythroid differentiation system that demonstrates induction of fetal globin gene expression and HbF production by 5-Aza.…”
mentioning
confidence: 99%
“…The induction of HbF synthesis is a promising strategy for the treatment of SCD [32,33]. The elevated levels of HbS and low levels of HbF in patients with SCD are related to the clinical severity of the disease and the early mortality of the patients.…”
Section: Induction Of Hbf Synthesismentioning
confidence: 99%
“…The butyrates have been shown to produce a sustained increase in the HbF concentrations of SCD patients, but their short half-lives and low bioavailability have limited their use clinically. Therefore, new derivatives of butyric acid, with superior bioavailability and increased halflives, are under investigation in animal models [33,55]. • Erythropoietin…”
Section: Induction Of Hbf Synthesismentioning
confidence: 99%
“…It was observed that activation of p38 MAPK (mitogen activated protein kinase) pathway and deactivation of ERK (extracellular signal regulated kinase) pathway led to an increase in higher expression of gamma globin gene and an increase in the level of HbF in treated cells. Increase in gamma globin gene expression and level of foetal Haemoglobin by activation of p38 MAPK pathway and deactivation of ERK pathway, has been observed in cells treated with different naturally occurring pharmacological and chemical compounds, such as cucurbitacin D, hydroxy urea, butyrate, an ethanol extract of Fructus trichosanthis, resveratrol [18,24,44,45]. On the basis of available literature, it may be concluded piceatannol treatment may increase the expression of gamma globin gene and result in increase in foetal Haemoglobin production in beta thalassaemia patients, because activation of p38 MAPK pathway and deactivation of ERK pathway have been confirmed in piceatannol treated cells [46].…”
Section: Assumption Based On Previous Studiesmentioning
confidence: 99%